2018
DOI: 10.1111/eje.12368
|View full text |Cite
|
Sign up to set email alerts
|

Exploring personality in Australian dentistry students: Implications for coping with a challenging degree

Abstract: This sample of dentistry students portrayed a profile of temperament and character similar to profiles of other health profession students with the intellectual ability and drives to undertake a competitive and challenging degree. Longitudinal studies are needed to track changes in personality throughout the degree. This would provide insight into how and when to best support students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Personality is also an important factor for stress perception and coping abilities . An Australian study amongst dental students found a personality profile similar to that of other students of health professions and concluded that observing changes in personality traits would help determine when to implement prevention strategies and support students . Another study demonstrated a significantly lower student satisfaction with the dental profession in Lithuania compared to Poland, both of which are investigated in the present study .…”
Section: Discussionmentioning
confidence: 58%
“…Personality is also an important factor for stress perception and coping abilities . An Australian study amongst dental students found a personality profile similar to that of other students of health professions and concluded that observing changes in personality traits would help determine when to implement prevention strategies and support students . Another study demonstrated a significantly lower student satisfaction with the dental profession in Lithuania compared to Poland, both of which are investigated in the present study .…”
Section: Discussionmentioning
confidence: 58%
“…Desire to be in a profession or calling is correlated with work‐related well‐being, career commitment and job satisfaction . In a similar study on dental students' personality, those whose first career preference was dentistry had higher levels of self‐directedness which is indicative of a strong sense of responsibility and goal orientation . Australian literature found high school students seeking professional occupations with notable reputations and income were less confident about making career‐related decisions.…”
Section: Discussionmentioning
confidence: 99%
“…25 In a similar study on dental students' personality, those whose first career preference was dentistry had higher levels of self-directedness which is indicative of a strong sense of responsibility and goal orientation. 27 Australian literature found high school students seeking professional occupations with notable reputations and income were less confident about making career-related decisions. These students were also found to be less 'career mature' or the ability to consider personal skills and interest for an occupation.…”
Section: Discussionmentioning
confidence: 99%
“…This study builds on a series of cross‐sectional publications investigating dentistry student's well‐being. This study represents a longitudinal follow‐up of students’ levels of depression, anxiety and stress over time, whilst controlling for the influence of personality and perceptions of the learning environment in dentistry 6,27,28 …”
Section: Introductionmentioning
confidence: 99%